2023
DOI: 10.1186/s12951-023-01871-w
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel armed with Bmp2 mRNA-enriched exosomes enhances bone regeneration

Abstract: Background Sustained release of bioactive BMP2 (bone morphogenetic protein-2) is important for bone regeneration, while the intrinsic short half-life of BMP2 at protein level cannot meet the clinical need. In this study, we aimed to design Bmp2 mRNA-enriched engineered exosomes, which were then loaded into specific hydrogel to achieve sustained release for more efficient and safe bone regeneration. Results Bmp2 mRNA was enriched into exosomes by se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Cell sheet technology can also prevent implantation-related inflammatory immune reactions, tissue collapse because of rapid degradation, and impaired tissue development in the context of slow scaffold degradation [ 60 ]. In this study, the porous structure of the GelMA hydrogel was selected as the basic scaffold material, which not only provides 3D growth space for cell sheet fragments but also maintains microenvironment stability and improves the activity of transplanted cells [ 61 , 62 ]. Through the optimization of GelMA preparation conditions, we found that 6% GelMA formed large pores after UV curing for 25 s, which are the most suitable conditions for the growth of cell sheets.…”
Section: Discussionmentioning
confidence: 99%
“…Cell sheet technology can also prevent implantation-related inflammatory immune reactions, tissue collapse because of rapid degradation, and impaired tissue development in the context of slow scaffold degradation [ 60 ]. In this study, the porous structure of the GelMA hydrogel was selected as the basic scaffold material, which not only provides 3D growth space for cell sheet fragments but also maintains microenvironment stability and improves the activity of transplanted cells [ 61 , 62 ]. Through the optimization of GelMA preparation conditions, we found that 6% GelMA formed large pores after UV curing for 25 s, which are the most suitable conditions for the growth of cell sheets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to direct injection, EVs can also be loaded on hydrogels, 204 206 scaffolds, 198 , 207 , 208 films, 209 , 210 or other biomaterials for bone repair (Fig. 5d ).…”
Section: The Potential Applications Of Evs In Osteoporosismentioning
confidence: 99%
“…However, the clinical use of natural exosomes has been restricted due to their weak activity, low yield, unpredictable side effects, and inefficient targeting ability . To overcome these limitations, exosome-laden hydrogels have been developed to augment their retention and stability at the site of bone defects. , However, most studies of exosome-laden hydrogels are slow-release models and do not evaluate the controlled release of exosomes. Furthermore, they may overlook the issue of reduced exosome bioactivity after prolonged storage in the hydrogels.…”
Section: Application Of Photoresponsive Hydrogels In Bone Tissue Engi...mentioning
confidence: 99%